OsSAPK2 Confers Abscisic Acid Sensitivity and Tolerance to Drought Stress in Rice - Lou, Dengji; Wang, Houping; Liang, Gang; Yu, Diqiu (Frontiers in Plant Science, 2017)
SNF 1-RELATED PROTEIN KINASE 2 (SnRK2) is a family of plant-specific protein kinases which is the key regulator of hyper-osmotic stress signalling and abscisic acid (ABA)-dependent development in various plants. Among the rice subclass-I and -II SnRK2s, osmotic stress/ABA–activated protein kinase 2 (SAPK2) may be the primary mediator of ABA signaling. However, SAPK2 has not been comprehensively characterized. In this study, we elucidated the functional properties of SAPK2 using loss-of-function mutants produced with the CRISPR/Cas9 system. The SAPK2 expression level was strongly upregulated by drought, high-salinity, and polyethylene glycol treatments. The sapk2 mutants exhibited an ABA-insensitive phenotype during the germination and post-germination stages, suggesting that SAPK2 had a pivotal role related to ABA-mediated seed dormancy. The sapk2 mutants were more sensitive to drought stress and reactive oxygen species than the wild-type plants, indicating that SAPK2 was important for responses to drought conditions in rice. An additional investigation revealed that SAPK2 increased drought tolerance in the following two ways: (i) by reducing water loss via the accumulation of compatible solutes, promoting stomatal closure, and upregulating the expression levels of stress-response genes such as OsRab16b, OsRab21, OsbZIP23, OsLEA3, OsOREB1 and slow anion channel (SLAC)-associated genes such as OsSLAC1 and OsSLAC7; (ii) by inducing the expression of antioxidant enzyme genes to promote ROS-scavenging abilities that will ultimately decrease ROS damages. Moreover, we also observed that SAPK2 significantly increased the tolerance of rice plants to salt and polyethylene glycol stresses. These findings imply that SAPK2 is a potential candidate gene for future crop improvement studies.